Genetic diversity and diallel analysis of elite popcorn lines - Rodrigues Castro, Camila (Revista Ciência Agronômica, 2021)
Popcorn is an important agricultural crop that is consumed as a snack food worldwide. In Brazil, the lack of cultivarswith high potential grain yield and popping expansion volume is a vital problem. Therefore, the present study aimed to evaluatethe genetic divergence among elite popcorn lines using amplifi ed fragment length polymorphism (AFLP) markers to estimate thegeneral and specifi c combining ability (GCA and SCA, respectively), and correlate the genetic distance with the SCA and hybridmeans. For the genetic divergence study, 45 popcorn inbred lines of different hybrids and varieties were evaluated. Subsequently, 10inbred lines were selected for diallel analysis; grain yield (GY) and popping expansion (PE) were evaluated in three environments.A wide variability of popcorn inbred lines was observed based on the AFLP markers. After evaluating the hybrids, a signifi canteffect was observed for GY and PE, with some experimental hybrids with higher potential GY and PE than the commercial cultivars.From the diallel analysis, a signifi cant effect was observed for GCA for GY and PE; therefore, the lines differed in the frequencyof favorable alleles, with promising inbred lines for forming hybrids or synthetic varieties. However, for SCA, no signifi cant effectwas observed for these traits. Genetic distance did not correlate with GY and Ŝij, demonstrating an absence of consistency in theprediction of heterotic groups for popcorn using AFLP markers.